Adaptation strategies in wildlife hunting practices among the Tehit Knasaimos Ethnic Group, South Sorong, Southwest Papua, Indonesia - RUDI APRIANTO MATURBONGS; ARLAN KAPISA; MELIZA S. WORABAI; MATHEUS BELJAI (Society for Indonesian Biodiversity, 2024)
Abstract. Maturbongs RA, Kapisa A, Worabai MS, Beljai M. 2024. Adaptation strategies in wildlife hunting practices among the Tehit Knasaimos Ethnic Group, South Sorong, Southwest Papua, Indonesia. Biodiversitas 25: 3309-3319. This research investigates the adaptation strategies employed by the Tehit Knasaimos Ethnic Group in South Sorong District, Southwest Papua Province, Indonesia to sustain their wildlife hunting practices. Employing a descriptive methodology that integrates both qualitative and quantitative approaches, the study focuses on the villages of Manggroholo and Sira. It explores how the community reconciles traditional hunting and fishing practices with the pressures of modern development by incorporating modern tools and economic practices. This analysis examines how traditional practices are adapted to meet the dual demands of cultural preservation and economic necessity. Key findings indicate a significant shift from traditional barter systems to cash-based transactions, highlighting the impact of modern economic integration on traditional economies. Additionally, a noticeable adoption of more durable materials in hunting and fishing gear suggests a move towards more sustainable practices that could reduce environmental degradation. Notably, the research emphasizes the continued relevance of cultural practices such as totemism and the management of sacred forests (hutan pamali), which play a pivotal role in wildlife conservation. The study further underscores the critical role of indigenous leadership and community collaboration in maintaining the sustainability of these practices. By fostering a communal approach to resource management, the Tehit Knasaimos community can navigate the challenges of external economic and environmental pressures. These insights contribute significantly to a broader understanding of how indigenous communities adapt to external challenges while preserving their cultural heritage and promoting ecological sustainability. This study enriches the discourse on sustainable development and offers valuable lessons on the resilience of indigenous adaptation strategies in the face of global change.